2018
DOI: 10.1007/s00038-017-1067-1
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of critical time intervention for abused women leaving women’s shelters: a randomized controlled trial

Abstract: ObjectivesTo examine the effectiveness of critical time intervention (CTI)—an evidence-based intervention—for abused women transitioning from women’s shelters to community living.MethodsA randomized controlled trial was conducted in nine women’s shelters across the Netherlands. 136 women were assigned to CTI (n = 70) or care-as-usual (n = 66). Data were analyzed using intention-to-treat three-level mixed-effects models.ResultsWomen in the CTI group had significant fewer symptoms of post-traumatic stress (secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
60
0
10

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(74 citation statements)
references
References 30 publications
1
60
0
10
Order By: Relevance
“…CTI showed little effect on mental health outcomes. However, a trial conducted among abused women reported significantly fewer symptoms of PTSD during follow-up (Adjusted MD -7.27, 95% CI -14.31 to -0.22, p = 0.04), but no effect on symptoms of depression or psychological distress [84]. In another RCT [85], families who received CTI showed mixed results on the frequency of children's internalizing and externalizing problems.…”
Section: Effects Of Critical Time Interventions (Cti)mentioning
confidence: 94%
See 1 more Smart Citation
“…CTI showed little effect on mental health outcomes. However, a trial conducted among abused women reported significantly fewer symptoms of PTSD during follow-up (Adjusted MD -7.27, 95% CI -14.31 to -0.22, p = 0.04), but no effect on symptoms of depression or psychological distress [84]. In another RCT [85], families who received CTI showed mixed results on the frequency of children's internalizing and externalizing problems.…”
Section: Effects Of Critical Time Interventions (Cti)mentioning
confidence: 94%
“…Two RCTs examined quality of life outcomes and found no significant impact of CTI over usual services at 9 months [81,84]. As well, when looking at substance-use outcomes, CTI was associated with non-significant reductions in cannabis and alcohol use [81].…”
Section: Effects Of Critical Time Interventions (Cti)mentioning
confidence: 99%
“…90 However, findings for children's mental health were mixed: children aged 1.5-5 years showed improvements in internalizing (β coefficient -3.65, 95% CI -5.61 to -1.68) and externalizing behaviours (β coefficient -3.12, 95% CI -5.37 to -0.86), whereas changes for children aged 6-10 years and 11-16 years were not significant. 93 There were no significant effects of critical time intervention on substance-use, 90 quality-of-life 90,92 or income-related outcomes. 96 Two trials reported mixed findings on hospital admission outcomes; in 1 study, allocation to critical time intervention was associated with reduced odds of hospital admission (OR 0.11, 95% CI 0.01 to 0.96) and total number of nights in hospital (p < 0.05) in the final 18 weeks of the trial.…”
Section: 29mentioning
confidence: 93%
“…A scoping review of the literature on interventions for homeless women (Christine Mathew, Bruyère Research Institute, Ottawa, Ont. : unpublished data, 2020) yielded 4 systematic reviews [153][154][155][156] and 9 randomized controlled trials (RCTs) 36,60,92,95,[157][158][159][160][161] that focused specifically on homeless and vulnerably housed women. Findings showed that PSH was effective in reducing the risk of intimate partner violence and improving psychological symptoms.…”
Section: Womenmentioning
confidence: 99%
See 1 more Smart Citation